Lessons from the English primary care sentinel network's response to the COVID-19 pandemic - de Lusignan, S; Hobbs, FR; Sheikh, A (Elsevier, 2023)
This Comment reflects our experience of deploying the Oxford-Royal College of General Practitioner's Research and Surveillance Centre (RSC), England's primary care sentinel network, in response to the COVID-19 pandemic.